Third-Party Litigation Funding: Legal Feasibility and Insights from Australia, the UK, and the US for Expanding Access to Justice in Indonesia - Herliana, Herliana (Faculty of Law, Sriwijaya University, Indonesia, 2025)
Access to justice is often hindered by financial constraints, preventing plaintiffs from pursuing legal claims. Third-Party Litigation Funding (TPLF) offers a potential solution by allowing external funders to finance litigation in exchange for a share of any awarded damages or settlement. By covering litigation costs, TPLF enables financially disadvantaged plaintiffs to seek legal redress, making it a crucial mechanism for expanding access to justice. However, unregulated TPLF poses risks, including the encouragement of frivolous claims, ethical concerns, and profit-driven motivations that may override legal merit. Indonesia currently lacks specific regulations governing TPLF, raising questions about its legal permissibility and practical implementation. This study examines TPLF frameworks in Australia, the United Kingdom, and the United States to derive insights that may inform the development of TPLF practices in Indonesia. Utilizing a normative legal research methodology based on secondary data, the study explores the opportunities and challenges of introducing TPLF into the Indonesian legal system. The findings indicate that while TPLF can be legally accepted in Indonesia, its application should be restricted to cases with broad public interest, such as environmental and consumer litigation. Furthermore, Indonesia’s ongoing efforts to enhance access to justice and the absence of explicit legal prohibitions present opportunities for the regulated adoption of TPLF. This research contributes to the discourse on litigation funding by providing recommendations for policymakers, legal practitioners, and stakeholders in shaping a fair and regulated TPLF framework in Indonesia.